IsomiRex: Web‐based identification of microRNAs, isomiR variations and differential expression using next‐generation sequencing datasets. Issue 16 (4th July 2013) - Sablok, Gaurav; Milev, Ivan; Minkov, Georgi; Minkov, Ivan; Varotto, Claudio; Yahubyan, Galina; Baev, Vesselin
Abstract : We present an open‐access web platform isomiRex, to identify isomiRs and on the fly graphical visualization of the differentially expressed miRNAs in control as well as treated library. The open‐access web‐platform is not restricted only to NGS sequence dataset from animals and potentially analyzes a wider dataset for plants, animals and viral NGS dataset supporting miRBase (version 19 supporting 193 species). The platform can handle the bloated amount of the read counts and reports the annotated microRNAs from plant, animal and viral NGS datasets. isomiRex also provides an estimation of the the isomiRs, of miRNAs with higher copy number relative to their mature reference sequences indexed in miRBase (version 19 supporting 193 species). Visually enhanced graphs potentially display differentially expressed isomiRs, which will help the user to demonstrate and correlate the abundance of the isomiR as a signature event to the specific condition. An additional module for estimating the differential expression has been implemented allowing the users to postulate the differential expression across the user input samples. The developed web‐platform can be accessed athttp://bioinfo1.uni‐plovdiv.bg/isomiRex/ . Abstract : Web‐based tool for miRNA characterization in NGS datasets. Allows for identification of miRNAs and isomiR sequences supporting 193 organisms. Automatic analysis of differential expression of the detected miRNAs.